Nekotorye aspekty povysheniya energeticheskikh potentsii organizma sportsmenov - Artemyeva, N. K. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The author of this article designed some special food additions for athletes performance's increasing, such as the "Enotonic","Solodoviy" and others. These food additions contain the important components, which are in lack in usual athlete ration. The aim of this study was to research an express and cumulative influence of the food additions to athlete's training efficiency. More than 90 athletes took part in the experiment. At the end of the experiment, the athletes, who received the food additions had shown the best results. The author concludes, that carefully selected chemical contents and quantity of biologically active agents in food additions, jointly with correct technology of using make a positive influence to athlete's metabolic processes, and optimize a performance increasing.